Theoretical analysis of stress intensity factor for two unequal collinear cracks subjected to internal pressure and compressive stress. (27th September 2021) - Zhang, Xianshang; Long, Qingming; Zheng, Tao; Zhu, Zheming; Wang, Meng; Hou, Peng
Abstract: In this paper, a new solution of the stress intensity factors (SIFs) for two unequal collinear cracks is developed considering internal pressure, friction and compressive stress. The complex stress function and elliptic integral function are used to obtain the analytical solution of the SIFs, and it shows a good agreement with the previous researchers' solutions and numerical results. The theoretical results show that the difference and interaction of the SIFs at cracks' tips are caused by crack geometry parameters, and they also indicate that the internal pressure leads to the SIFs of a mode I crack and affects the SIFs of a mode II crack because of friction.